PENERAPAN KEPUTUSAN HEDGING PADA SUATU PERUSAHAAN (STUDI KASUS SUB SEKTOR TAMBANG MINERAL BATUBARA YANG TERDAFTAR DI BEI TAHUN 2019 – 2022) - Nur Intannia Putri; Ahmad Setiawan Nuraya (Ibs Press, 2024)
This research was conducted to determine the influence of independent variables such as leverage, company size, cash flow volatility and liquidity on hedging decisions in coal mineral mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 - 2022. This research uses secondary data taken from the company's official website in the research. This research uses coal mineral mining sub-sector companies as a population for a period of 5 years. This research uses purposive sampling with the criteria that have been found and a total of 17 companies. The research uses the logistic regression analysis method and uses the IBM SPSS Statistics 26 application. The results of the test show that the independent variable leverage has a positive effect on hedging decisions, while the independent variables company size, cash flow volatility do not have a positive effect on hedging decisions, and the free variable liquidity does not have a negative effect on hedging decisions.